Household Water Treatment Practice and Associated Factors in Gibe District Southern Ethiopia: A Community Based Cross-Sectional Study - Bereket Tafesse; Tesfaye Gobena; Negga Baraki; Yohanis Alemeshet Asefa; Dechasa Adare Mengistu (SAGE Publishing, 2021)
Background: Household water treatment practice or managing water at the point-of-use provides a means of improving drinking water quality and preventing diarrheal diseases. However, evidence regarding household water treatment practice and associated factors in Ethiopia, particularly in Southern Ethiopia are limited. This study was, therefore, designed to assess household water treatment practice and associated factors among households in Southern Ethiopia. Methods: A community-based cross-sectional study design was conducted among 627 households in Southern Ethiopia. A stratified random sampling technique was used in this study and a pre-tested structured questionnaire was used to collect data about household water treatment practice and associated factors among selected households through face-to-face interviews. The data were analyzed using descriptive statistical tests and binary logistic regression was performed to assess the association between independent and dependent variables. Odds ratio with 95% confidence intervals were used to determine the level of association. Results: This study revealed that the level of household water treatment practice was 34.3% with 95% CI (30.7-38.1) and boiling was the most common method of household water treatment in the study area. Educational status of having formal education (AOR = 2.01, 95% CI = 1.34-3), withdrawing water from storage vessel by dipping (AOR = 1.86, 95% CI = 1.2-2.87) and frequency of fetching water 3 or more times and above a day (AOR = 2.65, 95% CI = 1.45-4.88) were significantly associated with household water treatment practice. Conclusion: Household water treatment practice is low in the study area. Educational status of having a formal education, drawing water by dipping, and those who collect their drinking water 3 or more times a day were predictors of household water treatment practice. Thus, efforts should be made to increase the level of household water treatment practice especially among those with no formal education and further studies should be conducted to understand the behavioral factors associated with household water treatment practice.